2021
DOI: 10.1101/2021.11.06.467539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-genome sequencing of Chinese native goat offers biological insights into cashmere fiber formation

Abstract: Cashmere evolved naturally in the goat, and almost all breeds of goat can produce more or less cashmere fibers. However, the genetic alterations underlying cashmere trait selection are still unclear.We sequenced 120 Chinese native goat including two cashmere goat breeds (Ujumain, Chaidamu) and six ordinary goat breeds (Jining Gray, Matou, Guizhou Black, Jintang Black, Yunnan Black Bone, Chengdu Brown). The genome-wide selective sweep of cashmere goat and ordinary goat revealed a novel set of candidate genes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The candidate genes for the wool traits identified in this study included IGF-1, TGFBR2, PDE3A, STK3, PRKCA, ZNF704 and EXT1. These genes have previously been associated with hair [30][31][32], cashmere [33,34] and wool [35][36][37]. In our study, the functional analysis indicated that the genes WAPL, ESR1 and IGF-1 were significantly enriched in the regulation of fibroblast proliferation (see Supplementary Materials), which is crucial for hair follicle formation [38].…”
Section: Discussionsupporting
confidence: 54%
“…The candidate genes for the wool traits identified in this study included IGF-1, TGFBR2, PDE3A, STK3, PRKCA, ZNF704 and EXT1. These genes have previously been associated with hair [30][31][32], cashmere [33,34] and wool [35][36][37]. In our study, the functional analysis indicated that the genes WAPL, ESR1 and IGF-1 were significantly enriched in the regulation of fibroblast proliferation (see Supplementary Materials), which is crucial for hair follicle formation [38].…”
Section: Discussionsupporting
confidence: 54%
“…The IGF1R gene governs the anagen phase by activating bone morphogenetic protein 4 (BMP4), which regulates stem cell expansion and thus hair follicle development (Castela et al, 2017). Han et al (2021) performed whole genome sequencing in 120 Chinese native goats (cashmere and ordinary goat breed) to determine the selection signals linked to cashmere fiber attributes. The studies identified the highest selection signals on chromosome 11, which included candidate genes ( DENND1A , LHX2 , and CRB2 ).…”
Section: Selection Signature Studies In Fiber‐producing Animalsmentioning
confidence: 99%
“…The IGF1R gene governs the anagen phase by activating bone morphogenetic protein 4 (BMP4), which regulates stem cell expansion and thus hair follicle development (Castela et al, 2017). Han et al (2021) and CRB2). The LIM homeobox 2 (LHX2) gene is associated with hair follicle development.…”
Section: Goamentioning
confidence: 99%